PROCESSING OF GELATIN AND ANIMAL GLUE FROM COW BONS AND STUDYING THEIR CHEMICAL AND SOME PHYSICAL AND FUNCTIONAL PROPERTIES - L. D.Al - Doori (Mesopotamia Journal of Agriculture)
Food grade gelatin and animal glue were extracted from cow bones. Three extraction methods were employed beging alkali , lime and acid . The acidic extraction was the best as far as quantity , quality and economey aspects The yield was 6.8 % , 2.51 % ash and 8.35 % moisture .It was found that gelatin appeared to have good properties comparing with imported and better than commercial especially solubility as far as jelling strength .However its setting time was lower than that of commercial and higher than that of imported gelatin , in addition to its viscosity was higher than that of sheet gelatin . Animal glue was recovered after gelatin isolation possessed good physical and functional properties comparing with commercial as far as solubility , viscosity and considerably stronger adhesive power